Exploring levels of student-athlete burnout at two Canadian universities - Dubuc-Charbonneau, Nicole M; Durand-Bush, Natalie (Canadian Journal of Higher Education, 2014)
The purpose of the current study was to examine the levels of burnout among student-athletes at two Canadian universities and to investigate whether there were significant differences related to gender, sport, year of university sport participation, academic year, and academic program. Burnout was measured by administering Raedeke and Smith’s (2001) Athlete Burnout Questionnaire to 145 student-athletes from various sports. Overall, 1.4% of the student-athletes had elevated burnout scores on all three subscales, and 17% scored high on two of the three subscales. No significant differences emerged with regards to year of varsity sport participation, academic year, or program. However, women had significantly higher levels of emotional and physical exhaustion than men. Significant differences also emerged in relation to levels of emotional and physical exhaustion, and of sport devaluation, when comparing various sports.